A validity exploration model related to the existence of the generic problem-solving competence - Lan Anh Nguyen Khoa; Mathew Courtney; Mark Wilson; Cuc Nguyen (IMEKO International Measurement Confederation, 2024)
There has been a growing focus on exploring the existence of Generic Problem-Solving competence across various fields, leading to heightened attention in this area. However, most of the previous and current approaches are limited in terms of validity and reliability. Thus, this paper aims to propose a new approach based on The Standards for Educational and Psychological Testing validity framework to investigate this matter. The investigation leads to the review of the conceptions of construct validity in educational measurement. The paper concentrates on the proposed validity exploration (VE) model, representing an elaborate enterprise and a serial, progressive procedure aligned with the content and structural validity aspects of The Standards framework. The PISA Computer-based Assessment was used as secondary data for this investigation.
Keywords: Competence (human resources); Psychology; Computer science; Social psychology; type of access: open access